2010
DOI: 10.1258/acb.2009.009146
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical risk factors for stone formation in a Scottish paediatric hospital population

Abstract: Background: Renal stones in children, although rare, may be associated with morbidity and renal damage. Scottish children have a different ethnic composition and diet compared with paediatric populations previously studied. Urinary stone promoters include calcium, oxalate and urate. Postulated inhibitors include citrate and glycosaminoglycans (GAGs). We tested the hypothesis that Scottish paediatric stone-formers have higher excretion of urinary stone promoters (calcium/ oxalate/urate) and/or lower excretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Like DeFoor et al, we have also shown calcium excretion to be significantly higher in subjects with more stones [12]. Other investigators have identified hypocitraturia as a common risk factor along with hypercalciuria [11;14;15], and still others have reported hypocitraturia alone to be the most important risk factor [43;44]. We have found no evidence for hypocitraturia among the stone formers we studied here.…”
Section: Discussionsupporting
confidence: 76%
“…Like DeFoor et al, we have also shown calcium excretion to be significantly higher in subjects with more stones [12]. Other investigators have identified hypocitraturia as a common risk factor along with hypercalciuria [11;14;15], and still others have reported hypocitraturia alone to be the most important risk factor [43;44]. We have found no evidence for hypocitraturia among the stone formers we studied here.…”
Section: Discussionsupporting
confidence: 76%
“…Depending on geographic, genetic and socioeconomic factors, different incidence rates and etiological factors are reported in children with renal stone disease [12,13]. If the diagnosis is delayed, renal stones may cause considerable morbidity and renal damage [1]. It has been reported that 4 to 11% of all cases of chronic renal failure in Turkey have been secondary to urinary stone disease [14,15] .Urinary stone disease is a considerable childhood health problem in many places of the world and in our country.…”
Section: Discussionmentioning
confidence: 99%
“…Urolithiasis in children is an important cause of morbidity worldwide [1]. Symptoms of urinary tract stones are often non-specific, particularly in infants and young children and the stones may remain asymptomatic for a long time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result was not confirmed by other studies. [50][51][52][53] Harangi et al 53 suggested that the role of GAGs in stone formation could be related not only to their level but also to their degree of sulfation in children. Turudic et al 54 found that the calcium independent oxalate/(citrate × glycosaminoglycans) ratio could be used as a marker for idiopathic calcium oxalate urolithiasis.…”
Section: Urinary Gags In Kidney Diseasesmentioning
confidence: 99%